Assessment of Mandibular Asymmetry Using the Orthopantogram and Posteroanterior Cephalogram: A Comparative Study - Novaira Waseem, Zubair Hassan Awaisi, Amna Malik (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: The objective of this study is to assess and correlate the measurements of mandibular asymmetries using a posteroanterior (PA) cephalogram and an orthopantomogram (OPG). . Materials & Methods: A comparative cross-sectional study was conducted in the Department of Orthodontics, Nishtar Institute of Dentistry, Multan. Orthopantomograms and posteroanteriorcephalograms were obtained from 66 patients aged between 12 and 35 years. Linear mandibular measurements were then identified and evaluated for discrepancies between the two imaging techniques. The comparison of orthopantomograms and posteroanteriorcephalograms involved a paired t-test to assess all linear mandibular parameters. To further compare orthopantomograms and posteroanteriorcephalograms, an independent sample t-test was conducted using SPSS version 22.0. Results: The mean age of the patients was 22.65 years, with a standard deviation (SD) of 1.68 years. The age range of the patients varied from 12 to 35 years, with the majority falling into two age groups: 12–25 years, which comprised 38 patients (58.46%), and 26–35 years, which included 28 patients (42.54%). In terms of gender distribution, 36 patients (54.55%) were male, while 30 patients (46.15%) were female. The mean length of the condyle (Co-Snp) on OPG was 1.3±0.92, whereas it was 2.05±1.683 on the PA céphalogram. The mean difference between the two methods was 0.09±0.19, and this difference was not statistically significant with a p-value of 0.432. Similarly, for the length of the ramus (Co-Go), the mean on the OPG was 1.85±0.90, while it was 2.40±0.95 on the PA Cephalogram. There was a moderate to strong positive correlation between the measurements of these mandibular features. Practical Implication: This suggests that asymmetry indices for the mandibular posterior regions can be reliably calculated from OPG data in the vertical dimension. However, it is essential for clinicians to be mindful of potential radiographic machine distortions when evaluating these measurements Conclusion: This study suggests that asymmetry indices for the mandibular posterior regions can be reliably calculated from OPG data in the vertical dimension. However, it is essential for clinicians to be mindful of potential radiographic machine distortions when evaluating these measurements Keywords: Orthopantomogram, Posteroanteriorcephalogram, Linear mandibular measurements, mandibular asymmetry,